Analisis Pemecahan Masalah Siswa dalam Operasi Hitung Penjumlahan Bilangan Bulat Siswa SMP Negeri 1 Kota Tambolaka - Dodo, Arista Ina; Lede, Yulius Keremata; Making, Samuel Rex M. (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of the research is to the determine students, problem solving in the operation of calculating of integers for students at SMP Negeri 1 Tambolaka City. This type of research is descriptive qualitative. The subject of this research are all students in class VIIB of SMP Neger 1 Tambolaka City, totaling thirty-six students. The object of a research in the aritmatic operation of adding integers to students SMP Negeri 1 Tambolaka City . The data colection techniques used were written test, interviews, and documentation. Based on the research above, it can be conluded that problem solving analysis of problem solving in the aritmatic operation of adding integers to students at SMP Negeri 1 Tambolaka City. In the problem solving indicator there are, 58.52% of students who understand the problem, 58.52% of students were able to prepare a solution plan,34.63% of students were able carry out plan, students were able to look again, student are able to see return there is 29.61%.